Pengaruh Penggunaan Sistem Informasi Manajemen Berbasis Digital pada Usaha Mikro Kecil dan Menengah - Laila Azizah; Muhammad Irwan Padli Nasution (Universitas 45 Surabaya, 2025)
The implementation of digital-based management information systems in Micro, Small, and Medium Enterprises (MSMEs) has become increasingly important in the era of globalization and the advancement of information technology. MSMEs in Indonesia play a vital role in the national economy, but the adoption of digital management information systems (MIS) faces several challenges. Key challenges include limited digital literacy, inadequate training programs, and insufficient technological infrastructure. However, the adoption of digital technology has great potential to improve efficiency and competitiveness of MSMEs. The main objective of this study is to analyze the impact of using digital-based management information systems on the development of MSMEs. This study uses a qualitative approach with a literature review method, examining existing research related to the use of digital MIS in the MSME sector. The results indicate that the implementation of digital-based MIS can transform the operational paradigm of MSMEs towards sustainable growth. This system helps MSMEs manage business information, improve operational efficiency, and accelerate decision-making processes. With the right adoption of MIS, MSMEs can be better prepared to compete in the global market, even though challenges such as limited access to technology and training still need to be addressed.